ISOLASI DAN IDENTIFIKASI SENYAWA STEROID FRAKSI KLOROFORM DARI FRAKSINASI EKSTRAK METANOL DAUN KEREHAU (Callicarpa longifolia Lam.) - Arie Novadiana; Erwin -; Subur P Pasaribu (JURNAL KIMIA MULAWARMAN, 2014)
Kerehau (Callicarpa longifolia Lam.) is one of the biodiversity used as traditional medicine by one of the indigenous tribes of Borneo, called Dayak Tunjung. The purpose of this study was to determine about toxicity level of the Kerehau leaves (Callicarpa longifolia Lam.) to larvae shrimps (Artemia Salina Leach) and to determine the content of the active compounds contained in the Kerehau leaves (Callicarpa longifolia Lam.). The research was conducted by extracting samples with methanol and then concentrated by rotary evaporator. Total extract fractionated with n-hexane and chloroform, and then column chromatography applicated to chloroform fraction. Phytochemicals and BSLT have been test to Isolates chromatography results, total extract and chloroform extracts to determine the level of toxicity, FTIR analysis was also performed to isolate the results of Chromatography. Based on the results test of phytochemical compounds secondary metabolites of Kerehau leaves (Callicarpa longifolia Lam.) indicated that the methanol extract containing steroid compounds, phenolics, and flavonoids. Chloroform fractions containing flavonoids and steroid compounds. Isolates Chloroform fraction containing Steroids compounds. On Brine Shrimp Lethality Test, death of larvae shrimps (Artemia Salina Leach) were recorded and processed using SAS Probit analysis to determine the value of Lethal Concentration (LC50) to the value of each is, in chloroform isolates with LC50 values of 96.4096 ppm, chloroform extract had LC50 values of 104.1878 ppm and methanol extract had LC50 values of 485.1681 ppm. In Chloroform fraction separation and purification using column chromatography and recrystallization techniques to produce pure compound that is found in fractions A.f. The compounds were characterized by FTIR spectrometer spectroscopy. Based on FTIR analysis of the isolates showed chloroform fraction compound characterization using IR spectrophotometer is IR λmaks cm -1 : 3248.12; 2862.36; 2939.52; 2607.76; 2345.44; 1458.18;1496.76; 1597.06; 1172.72; 1226.73; 1288.45; 1658.78; 1095.57; 1002.98, and 941.26. Based on the results obtained isolates suspected compound is a steroid class of sterols.Keywords : Kerehau, Callicarpa longifolia Lam., toxicity test, Phytochemical test, chloroform, and Steroid